Of women, outcastes, peasants, and rebels : a selection of Bengali short stories - Bardhan, Kalpana (University of California Press, 1990)
Until now the large body of socially focused Bengali literature has remained little known to Western readers. This collection includes some of the finest examples of Bengali short stories-stories that reflect the turmoil of a changing society traditionally characterized by rigid hierarchical structures of privilege and class differentiation. Written over a span of roughly ninety years from the early 1890s to the late 1970s, the twenty stories in this collection represent the work of five authors. Their characters, drawn from widely varying social groups, often find themselves caught up in tumul.